Analysis of Factors Affecting Motivation of Manager Work - Lbn. Raja, Togu Harlen; n, Sofiya (International Journal of Engineering and Technology, 2018)
Companies in running their operations must be supported by the availability of reliable human resources that can work well in order to create a good company performance. Characteristics of work have a strong relationship in directing the motivation of the manager's work so that managers will have the achievement of the results of activities that are supported by the characteristics of the work of its employees. Motivation will move when all employees working in the company really feel a comfortable organization climate and all employees have different skills so that employee shortcomings can be met with different employee skills. The role of managers is needed in moving employee motivation through various efforts of managers in moving employee work motivation is expected to get better and better. Organizational climate within the company will be created by the interaction between fellow employees and between employees with superiors that occur so far where the behavior and attitude of employees will be formed with the climate organization. Organizational climate is very important to be discussed at this time because the organizational climate will create an atmosphere of comfort of people working within the company that can encourage employees to work sincerely so that the achievement of corporate goals can be achieved well within a predetermined time through the decision of the company's work meeting. From result of research can be explained that job characteristics have relation to work motivation of manager equal to 60% and organization climate also have relation to work motivation manager equal to 34%. Then simultaneously can be explained that the two independent variables (work characteristics and organizational climate) have a relationship to the dependent variable (work motivation) of 76%.Â